Помогите пожалуйста! Заранее спасибо!

  • 1.a)0,5(x²-16)=0,5(x-4)(x+4)
    б)3(x³+27y³)=3(x+3y)(x²-3xy+9y²)
    в)-0,5x(-4xy+x²+4y²)=-0,5x(x-2y)²
    2.a)(252-251)(252+251)=1*503=503
    б)(252+48)²=300²=90000
    в)(78+22)(78²-78*22+22²)/(78²-78*22+22²)=100
    3.a)11b(4a²-49b²)=11b(2a-7b)(2a+7b)
    б)2(x-3y)-(x-3y)²=(x-3y)(2-x+3y)
    в)1-x²-a²+2ax=1-(a-x)²=(1-a+x)(1+a-x)
    4.x²(x+2)-9(x+2)=0
    (x+2)(x-3)(x+3)=0
    x=-2, x=3, x=-3
    5.(7+1)(7²+1)(7^4+1)(7^8+1)(7^16+1) домножим на (7-3)
    (7-1)*(7+1)(7²+1)(7^4+1)(7^8+1)(7^16+1)=(7²-1)(7²+1)(7^4+1)(7^8+1)(7^16+1)=
    (7^4-1)(7^4+1)(7^8+1)(7^16+1)=(7^8-1)*(7^8+1)(7^16+1)=(7^16-1)(7^16+1)=7^32-1
    (7+1)(7²+1)(7^4+1)(7^8+1)(7^16+1)=(7^32-1)/(7-1)=(7^32-1)/6
    1/6*7^32-(7^32-1)/6=1/6*7^32-1/6*7^32+1/6=1/6
    6.7^2n+1+2^2n+1=(7+2)(7^n-…………………+2^n)
    Так как (7+2)=9 делится на3, то и все делится на 3
    7. х²=а⇒а²-3а+1=0
    D=9-4=5
    a1=(3-√5)/2 U a2=(3+√5)/2
    x²=(3-√5)/2U  x²=(3+√5)/2
    x^4-3x²+1=(x²-3+√5)(x²-3-√)
    8.(782-1)(783-1)(782+1)(783+1)+1=(782-1)(782+1)(782-1)(783-1)(783+1)=
    (782²-1)(783²-1)+1=(782*783)²-782²-783²+1+1


  • По сути формула а^2-b^2=(a-b)(a+b)
    подставим  (252-251)(252+251)=503